The impacts of social networking sites on students' social life / Noor Edayu Mohd Yusoff and Nur Diyana Abd. Rahim - Mohd Yusoff, Noor Edayu; Abd. Rahim, Nur Diyana (2012)
Social networking site is a website that enables users to create their own profiles and form relationships with other users in an online setting. This site interactivity and multifunction such as creating profiles, updating status, posting comments and private messages attracted people to use the site and the usage had increased from year to year. However, social networking sites are affecting user's social life when users spent most of the time on the site and affect the user's time with family and friends. Hence, users became isolated, depress, lonely and less talkative. This happens when users start ignoring their surrounding and spent most of their time on the site. Therefore, this study aims to explain the impacts of social networking sites on user's social life. This study aims to provide the discussion on the above impacts by reviewing the past literatures and suggestions will be made for future improvements.